2021
DOI: 10.1128/spectrum.00228-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Eimeria tenella Microneme Protein (EtMIC8)

Abstract: Microneme proteins (MICs) of Eimeria tenella play key roles in motility, migration, attachment, and invasion processes. More than 20 apicomplexan parasite’s MICs have been identified, with nine Eimeria MICs being reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…E. tenella Shandong strain (SD-01) was maintained and propagated in our laboratory (Liu et al 2014 ). Unsporulated oocysts, sporulated oocysts, sporozoites, and merozoites were obtained as previously described (Zhao et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…E. tenella Shandong strain (SD-01) was maintained and propagated in our laboratory (Liu et al 2014 ). Unsporulated oocysts, sporulated oocysts, sporozoites, and merozoites were obtained as previously described (Zhao et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dexing Ma realized that specific L peptides, competing with E. tenella rhotryneck protein 2 (EtRON2) to bind EtAMA1 located on the surface of ascospores, inhibited the parasite's invasion of cells ( 35 ). It was shown that EtSTP protein acts mainly in the developmental and reproductive stages of the parasite and that the ability of ascospores to invade cells was significantly reduced by anti-rEtSTP antibody treatment ( 36 ). Anti-EtMIC8 antibodies significantly increase the rate of adhesion to host cells and reduce the rate of invasion of ascospores into host cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has shown that humoral immunity is crucial for combating coccidial infections (Constantinoiu et al 2008 ; Yuan et al 2022 ; Ding et al 2004 ; Zhao et al 2021a , b ). Serum IgG levels in the immunized rEmMIC2 and rEmMIC3 protein groups were significantly higher than those in the control group, confirming that rEmMIC2 and rEmMIC3 proteins induced humoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…They are secreted by microneme organelles that promote adhesion between parasites and the surface of host cells and perform the dynamics required for host cell invasion (Carruthers and Tomley 2008 ). Microneme proteins were found to effectively protect hosts from parasites in Toxoplasma gondii and chicken coccidia (Lee et al 2018 ; Sathish et al 2011 ; Zhao et al 2021a , b ); however, no studies have been reported on rabbit coccidia.…”
Section: Introductionmentioning
confidence: 99%